2002
DOI: 10.1016/s0895-7061(02)02980-1
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of drospirenone/17-β-estradiol in hypertensive postmenopausal women receiving enalapril1

Abstract: Our results suggest a significant additive BP-lowering effect of DRSP/E2 on both systolic and diastolic BP in hypertensive postmenopausal women receiving ENA, consistent with an antimineralocorticoid effect. DRSP/E2, a HRT with antimineralocorticoid effects, could offer a novel potential mechanism for reducing cardiovascular end points in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0
3

Year Published

2005
2005
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 29 publications
4
31
0
3
Order By: Relevance
“…However, one cannot rule out the possibility of a natural ageing effect, such as that observed in the Framingham Heart Study [51], given the absence of a control group or defined endpoints. A number of well-designed trials (see Table 2) have consistently demonstrated a significant blood pressure-lowering effect with DRSP plus E2 in postmenopausal women [43,[54][55][56]. This is consistent with the potent anti-aldosterone activity of DRSP.…”
Section: The Effect Of Drsp On Blood Pressuresupporting
confidence: 56%
See 1 more Smart Citation
“…However, one cannot rule out the possibility of a natural ageing effect, such as that observed in the Framingham Heart Study [51], given the absence of a control group or defined endpoints. A number of well-designed trials (see Table 2) have consistently demonstrated a significant blood pressure-lowering effect with DRSP plus E2 in postmenopausal women [43,[54][55][56]. This is consistent with the potent anti-aldosterone activity of DRSP.…”
Section: The Effect Of Drsp On Blood Pressuresupporting
confidence: 56%
“…E2/DRSP significantly reduced 24 h mean (±S.E.) SBP by 9 mmHg (±1.4) and DBP by 5 mmHg (± 1.2) from baseline (both P < 0.05), whereas no change in blood pressure was observed in the placebo plus enalapril group [54]. These findings show that E2/DRSP has added benefits on blood pressure when used in combination with other anti-hypertensive agents.…”
Section: The Effect Of Drsp On Blood Pressurementioning
confidence: 69%
“…The estimated sample SD of 11 mm Hg used in the calculation was obtained from the results of a previous study. 17 The sample size calculation was based on an assumed dropout rate of 10%.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…14 -16 DRSP/E2 has been shown to have significant antihypertensive effects in a shortterm study of postmenopausal, hypertensive women treated with enalapril. 17 When compared with other hormone therapies and oral contraceptives, DRSP yields a much greater rise in plasma aldosterone 14 -16 in response to the antimineralocorticoid effect of the compound.…”
mentioning
confidence: 99%
“…During its development for relief of menopausal symptoms, DRSP/E2 was shown to have significant antihypertensive effects in studies of postmenopausal, hypertensive women alone or in combination with enalapril. [17][18][19] Furthermore, DRSP/E2 was found to have a significant antihypertensive effect in patients with and without type 2 diabetes mellitus and concomitant use of angiotensin-converting enzyme inhibitors and angiotensin receptor antagonists. 20 When compared with other hormone therapies and oral contraceptives, DRSP results in a significantly greater increase in plasma aldosterone 14 -16 in response to the antialdosterone effect of the compound.…”
mentioning
confidence: 97%